VD_FINDINFO Décision / 2016 / 531 vom 16. Juni 2016 - VD Tribunal cantonal (2016)
CLASSEMENT DE LA PROCÉDURE, TORT MORAL, INDEMNITÉEN GÉNÉRAL, AVOCAT | 429 al. 1 let. a CPP (CH), 429 al. 1 let. c CPP (CH)